Teaching geography on matters of gender and sexuality / sexual orientation -Escola Padre José Theisen - Gabriel de Souza (Universidade Estadual de Alagoas, 2021)
In a culture that privileges the cisgender and heterosexual person, especially men, individuals who do not fit the sexual and gender pattern are treated as inferior. The general objective of the article is to contribute to the reflection about how teachers, specifically Geography, can collaborate for the transformation of the school space, which must belong to all, everyone and everyone, regardless of gender and sexual orientation. To fulfill this objective, the specific objectives are: to associate the teaching of Geography to the theme, to discuss about the social function of the school and to present possibilities of cartographic approach to issues of gender bias and LGBTphobia from school. In order to achieve the proposed objectives, a bibliographic survey was previously carried out on the theme of gender and sexuality and on citizenship and diversity at school, by authors and authors from geography and also from other areas of knowledge. The fieldwork was carried out at the Padre José Theisen Municipal School, located in the municipality of Craíbas, state of Alagoas. At school, the 9 ° Unique class was selected to carry out a cartographic activity, using pre-selected emojis that indicated the student's interpretation of the feeling that the offended groups may have when they are in the places inside the school . The methodology used to analyze the responses found in this activity was quantitative. The most used emojis were anger and fear. Through cartographic activity, it was possible to work prejudice spatially within the school, in addition to reflecting on the concept of place, which is so important in theindividual's life.